ANALISIS DETERMINAN ISLAMIC HUMAN DEVELOPMENT INDEX (I-HDI) DI NEGARA ANGGOTA ORGANISASI KERJASAMA ISLAM - Mardianto, Dedi (Institut Agama Islam Negeri (IAIN) Bone, 2023)
This study aims to determine the factors that influence the Islamic Human Development Index (I-HDI) in the Member States of Islamic Cooperation for the period 2010 to 2019. This study uses a quantitative method with a panel data approach (Common Effect Model) as the best model after carried out the specification of the test model. The type of data used is secondary data obtained from the World Bank which is then processed using statistical software eviews 10. The results show that the variable government spending in the health sector and the corruption perception index have a significant positive effect on I-HDI in the OCI countries while for the variable government spending in the education sector has a negative effect and the FDI variable does not have a significant effect on I-HDI in the OIC countries in 2010 to 2019